Knowledge base for the systematic design of wet cooling towers. Part II: Fill and other design parameters - Mohiuddin, A. K. M.; Kant, K. (Elsevier Science Ltd and IIR, 1996)
This paper describes the final part of the detailed methodology for the thermal design of wet, counterflow and crossflow types of mechanical and natural draught cooling towers. This part includes the following design steps: the fill or packing, total packed height and the number of decks, water and air loading, pressure drop across the packing, natural draught tower, fan design for a mechanical draught cooling tower, blowdown and make-up water rate, water distribution systems and drift eliminators. Different empirical relations and assumptions are used in this part of the design procedure.